Staging revolution : artistry and aesthetics in model beijing opera during the cultural revolution - Fan, Xing (Professor of Asian Theatre and Performance Studies) (Hong Kong University Press, 2018)
Staging Revolution refutes the deep-rooted notion that art overtly in the service of politics is by definition devoid of artistic merits. As a prominent component shaping the culture of the Cultural Revolution, model Beijing Opera (jingju) is the epitome of art used for political ends. Arguing against commonly accepted interpretations, Xing Fan demonstrates that in a performance of model jingju, political messages could only be realized through the most rigorously formulated artistic choices and conveyed by performers possessing exceptional techniques. Fan contextualizes model jingju at the in.